Effect of pulsed electric current treatment on corrosion of structural metals - Babutskii, A.I.; Chrysanthou, A.; Ioannou, J. (Проблемы прочности, 2009)
Results of corrosion tests of some structure metals previously treated using pulsed electric current of high density are presented. According to the data obtained, the treatment substantially affects corrosion of metals. In cases of HSLA steel and 5182 aluminum alloy, an increase of corrosion resistance occurs, whereas the same treatment causes a dramatic reduction of corrosion resistance of 5754 aluminum alloy.